2018
DOI: 10.1002/ir.20275
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Field Specificity and Variation in the STEM Gender Gap

Abstract: What can we learn by considering differences in women across STEM fields? Following a discussion of theoretical perspectives on disciplinary classification and a review of literature on women across STEM, this chapter uses nationwide survey data to highlight the unique nature of women intending to major in biological science, computer science, engineering, math/statistics, and physical science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…It has also been suggested that women are more likely to work in human-centered fields [50][51][52]. We can certainly observe corroboration of this hypothesis in our data, with CS education and HCI as the two fields with the highest FAR, followed by WWW and multimedia, which also put the human in the center of the research.…”
Section: Discussionsupporting
confidence: 87%
“…It has also been suggested that women are more likely to work in human-centered fields [50][51][52]. We can certainly observe corroboration of this hypothesis in our data, with CS education and HCI as the two fields with the highest FAR, followed by WWW and multimedia, which also put the human in the center of the research.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, we must take into account that different fields attract or retain women at different rates. For example, a number of studies posited that women are more likely to work in human-centered fields [76][77][78]. The higher FARs we observed in human-computer interaction and CS education appear to confirm this observation for CS fields.…”
Section: Related Worksupporting
confidence: 75%
“…Finally, we must take into account that different fields attract or retain women at different rates. For example, a number of studies posited that women are more likely to work in human-centered fields [ 79 81 ]. The higher FARs we observed in human-computer interaction and CS education appear to confirm this observation for CS fields.…”
Section: Related Workmentioning
confidence: 99%